Exploration of the Dissemination and Development of Guzheng Art in the New Era - Zhang, Surong (International Journal of Social Sciences and Public Administration, 2024)
With the development of the times and social changes, guzheng art, as an excellent traditional music culture in China, is facing new challenges of dissemination and development. The purpose of this paper is to analyse the communication status of guzheng art in the context of the new era, discuss the challenges and opportunities of its development, and propose strategies for innovation and development. Firstly, through the analysis of traditional and modern communication channels, it reveals the problems that exist in the communication process of guzheng art. Secondly, it discusses the impact of social change, cultural diversification and technological development on guzheng art, as well as the challenges and opportunities it faces. Then, the innovation and development strategies of guzheng art in the new era are proposed in terms of education promotion, work innovation, media communication and activity exchange. Then, through case analysis, it summarises the successful experiences of the dissemination and development of guzheng art at home and abroad, and discusses its inspiration for the development of guzheng art in China. Finally, this paper summarises the current situation and challenges of the dissemination and development of guzheng art in the new era, and looks forward to the future development trend of guzheng art.